On the ability of oyster mushroom (Pleurotus sajor-caju) confering changes in proximate composition and sensory evaluation of chicken patty - Wan Rosli, W. I.; Solihah, M.A.; Mohsin, S. S. J. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The proximate composition and sensory evaluation of chicken patties incorporated with various levels of grey oyster mushroom (Pleurotus sajor-caju, PSC) were studied. The chicken patties were formulated with either 0%, 25% or 50% of fresh PSC. Results show chicken patty formulated with 25% PSC had protein content of 17.46% lower than the control patty which had 18.13% but it was not significant. However, protein content reduces significantly when chicken meat being replaced with 50% PSC. Meanwhile, both cooked chicken patties containing 25% and 50% PSC significantly recorded lower concentration of fat at 10.67% and 7.15%, respectively. In addition, patty incorporated with 25% PSC had moisture content of 56.91% which is significantly lower than patty formulated with 50% which had moisture of 58.80%. In the sensory evaluation, there were no differences recorded in all sensory attributes of PSC-based patties judged by untrained panellists. The reduction of sensory scores for springiness and juiciness attributes were observed parallel with the level of PSC used in the patty formulations due to the higher moisture content of fresh PSC used in the formulation. Incorporation of ground PSC to replace partially chicken meat reduces fat and ash but increase moisture content of cooked patties. The addition of PSC at 25% to partially replace chicken meat can be recommended for the purpose of lowering production cost and fat content while unchanging the protein content. On the other hand, incorporation of 50% of PSC in chicken patties reduces all proximate composition except for moisture content but maintaining the overall acceptability of chicken patties.